Parental Emotion-Focused Behaviors Moderate the Relationship between Perceptual Sensitivity and Fear Reactivity in Anxious Children - Woodward, Emma C. (Child Psychiatry Hum Dev, 2020)
This investigation examined the synergistic role of parental emotion-focused socialization behaviors and children’s perceptual sensitivity on children’s fear reactivity. A sample of 105 children with anxiety disorders (8–12 years; M = 10.07 years, SD = 1.22; 57% female) and their clinically anxious mothers (M = 39.35 years, SD = 7.05) completed an assessment battery that included a diagnostic interview and questionnaires regarding anxiety symptoms, perceptual sensitivity, and emotion socialization behaviors; children also completed a 5-minute, videotaped speech task, and rated their fear levels before and after the task. Analyses revealed a significant interaction between perceptual sensitivity and emotion-focused strategies predicting fear change scores from pre- to post-speech. Higher perceptual sensitivity was related to greater reductions in fear from pre- to post- speech (adjusting for pre-speech fear level), yet only among anxious children whose mothers reported high use of emotion-focused strategies. Maternal emotion-focused socialization strategies may increase anxious children’s ability to modulate their affective responses during stressful situations.